Comparative Analysis of Anatomical Differences in Upper Airways and Soft Tissues Between Healthy Individuals and Those with Sleep Disorder Patients - Kanwal Saeed, Tanzeela Khan, Afsheen Khan, Mamoona Shoukat, Hasan Shami, Zaffar Iqbal Malik, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Obstructive sleep apnea (OSA) and other sleep disorders are associated with anatomical differences in the upper airway and soft tissues, leading to airway obstruction and breathing difficulties. Identifying these variations can aid in early diagnosis and treatment planning. Objective: To compare anatomical differences in the upper airway and soft tissues between healthy individuals and patients with sleep disorders. Study Design and Setting: This was a comparative cross-sectional study conducted at Department of Anatomy DIMC, DUHS Karachi over six months. Methodology: A total of 140 patients were included, with 70 diagnosed sleep disorder patients and 70 healthy controls. Anthropometric data, cephalometric measurements, and advanced imaging were used to assess airway dimensions, soft tissue thickness, and craniofacial structures. Polysomnographic findings and Mallampati classification were also recorded. Data were analyzed using SPSS, with p-values < 0.05 considered statistically significant. Results: Patients with sleep disorders had significantly higher BMI (29.6 ± 3.4 kg/m²) and neck circumference (40.1 ± 3.2 cm) compared to controls (p < 0.05). Cephalometric analysis revealed reduced posterior airway space, increased soft palate thickness, and larger tongue volume in affected individuals. Imaging findings showed a smaller minimum airway cross-sectional area (95.6 ± 17.2 mm²) and greater lateral pharyngeal wall thickness in sleep disorder patients (p < 0.05). Polysomnographic results confirmed worsening oxygen desaturation and reduced sleep efficiency in severe cases. Conclusion: Significant anatomical differences in airway structures contribute to sleep disorders. Recognizing these variations can improve diagnostic accuracy and guide targeted interventions. Keywords: Airway dimensions, cephalometric analysis, craniofacial morphology, obstructive sleep apnea, polysomnography, sleep disorders, soft tissue thickness